Bangladesh Climate Change Adaptation Survey (BCCAS), Round I - International Food Policy Research Institute; Data Analysis and Technical Assistance; University of Bonn (International Food Policy Research Institute, 2014)
The Bangladesh Climate Change Adaptation Survey (BCCAS), Round I contains data on 800 farming households. It provides information on demographic characteristics, social capital, land tenure, crop and livestock management, input use, extension, incidence of climatic shocks in the last five years and adaptation options. The survey was conducted from December 2010 to February 2011, covering data from the previous production year. It covers households in the 7 broad agroecological zones a s grouped by the Bangladesh Center for Advanced Studies. (2014)